Effect of Lukabarasi Morphology on the Quality of Written Kiswahili Among Secondary School Students in Kakamega North Sub County - Chenenje, Solomon Luvonga (Journal of Linguistics, Literature, and Language Teaching (JLLLT), 2024)
Although there is a resemblance in some of the Lukabarasi and Kiswahili lexical items, some morphological structures are incompatible and, consequently, cause errors or mistakes. The main objective of the study is to analyze the effect of Lukabarasi morphology on the quality of written Kiswahili language among secondary school students in the Kakamega North sub-county. Specific objectives are to scrutinize the main agents of transfer of errors from L1 to L2 and how Lukabarasi affects the quality of written Kiswahili in the Kenya Certificate of Secondary Education examination. The study was analyzed within the framework of Interlanguage theory by Larry Selinker (1972), which stated that during the acquisition of a second language, the learner transfers the rules from the L1 to L2, and if the two have distinct structures, the errors occur in the L2. Questionnaires were channelled to 17 teachers and 76 form-one students who were selected purposively from 10-day schools until the saturation stage was attained. The oral interview was applied to 25 parents of some of the students who were selected based on the convenience sampling technique. The study revealed that to express politeness in communication, Lukabarasi speakers add the suffix (-kho) and (-nga) to the verbs in the present simple tense. When such rules are transferred from Lukabarasi to Kiswahili, morphological errors occur, and during prefixation in Kiswahili, some Kabarasi students use a instead of ha. This alteration of (-h-) renders the lexical items erroneous. The study further found that parents are the main agents of the transfer of errors from L1 to L2 in the early years, which makes it difficult to correct the learner at the secondary school level. Therefore, Lukabarasi morphology affects the quality of written Kiswahili negatively. It is not unique to Lukabarasi but also to other dialects of the Luhya speech community.